Neurological Adverse Events Associated with the Use of Janus Kinase Inhibitors: A Pharmacovigilance Study Based on Vigibase - Sunny Park; Min Kyu Kim; Sung Bin Park; Dong Hyeok Kim; Young Joo Byun; Soo An Choi (Pharmaceuticals)
Background: Janus kinase (JAK) inhibitors are a new class of targeted therapies that block cytokines and the signal transduction and activators of transcription (STAT) pathway. However, post-marketing surveillance studies have led to revised recommendations, highlighting potential serious heart-related events and cancer risk of JAK inhibitors. Here, we aimed to determine the neurological adverse events (AEs) of JAK inhibitors (tofacitinib, ruxolitinib, and baricitinib) based on a global real-world database. Methods: We analyzed individual case safety reports from the Uppsala Monitoring Center from January 1968 to 4 April 2022. A disproportionality analysis was performed using the proportional reporting ratio (PRR), reporting odds ratio (ROR), and information component (IC) to detect signals. Signals were classified according to the hierarchy of the Medical Dictionary for Regulatory Activities (MedDRA). Additionally, a stratified disproportionality analysis by age group and sex was performed for major AEs. Results: A total of 30,051,159 reports for all drugs were analyzed in this study. Among 105,798 reports of tofacitinib, 14.1% (14,863 reports) were neurological AEs. For ruxolitinib and baricitinib, 14.5% (6317 reports) and 10.2% (1216 reports) were neurological AEs, respectively. Various neurological AE signals were detected for tofacitinib and ruxolitinib, with memory impairment exhibiting the highest number of reports and a positive signal in the stratified disproportionality analysis by age group. Baricitinib did not reach the signal detection threshold. Conclusions: This study suggests the potential for neurological AEs, including memory impairment, associated with tofacitinib and ruxolitinib use based on a real-world database.